Timbba:An Innovation to Reduce Leakage and Frauds for Sawmills - Jain, Deepak (Indian Journal of Computer Science, 2020)
There are many issues that sawmill owners face such as fraud in consignment, leakage in material, and altered data during the journey of wood logs through various ports and sawmills. This paper discusses how TimbbaÂ® solves these problems and increases efficiency, and eliminates losses for sawmill owners.